2017
DOI: 10.1515/cpe-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Assessing Haemolysis in a Rotary Blood Pump Using Large Eddy Simulations (LES)

Abstract: The opportunity to assess haemolysis in a designed artificial heart seems to be one of the most important stages in construction. We propose a new method for assessing haemolysis level in a rotary blood pump. This method is based on CFD calculations using large eddy simulations (LES). This paper presents an approach to haemolysis estimation and shows examples of numerical simulation. Our method does not determine the value of haemolysis but allows for comparison of haemolysis levels between different artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Most grid convergence studies of blood pumps on the grid resolution are based on the URANS method to date. In a recent study, Torner et al 15 studied the flow field and explored turbulent flow structures in an axial blood pump using large eddy simulation (LES) 16–18 . Low dissipation and high accuracy are the characteristics of LES, and the sensitivity to the grid was found to be considerably higher than that of URANS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most grid convergence studies of blood pumps on the grid resolution are based on the URANS method to date. In a recent study, Torner et al 15 studied the flow field and explored turbulent flow structures in an axial blood pump using large eddy simulation (LES) 16–18 . Low dissipation and high accuracy are the characteristics of LES, and the sensitivity to the grid was found to be considerably higher than that of URANS.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Torner et al 15 studied the flow field and explored turbulent flow structures in an axial blood pump using large eddy simulation (LES). [16][17][18] Low dissipation and high accuracy are the characteristics of LES, and the sensitivity to the grid was found to be considerably higher than that of URANS. Huo et al 19 employed both the LES and RANS to investigate the flow field in the FDA pump using three grids of 4.2, 8.3, and 19.5 million, respectively.…”
mentioning
confidence: 99%
“…Medvitz et al 27 showed that LES can provide detailed flow field and wall-strain rate data for a positive displacement LVAD. Szwast et al 28 used the LES model to model energy dissipation and hemolysis in a centrifugal blood pump. Gross-Hardt et al 29 studied the FDA benchmark blood pumps using three common turbulence modeling approaches: laminar, RANS (SST model), and SBES (stress-blended eddy simulation, a hybrid LES-RANS).…”
Section: Introductionmentioning
confidence: 99%
“…The test results of Sallam and Hwang 45 alone were corrected several times by other research groups through a modified calculation. 46 , 49 , 50 , 53 Szwast et al 54 propose as an alternative to haemolysis risk assessment the determination of energy dissipation (points where flow energy is lost), which can be determined by large eddy flow simulation (LES), a special form of CFD. The Food and Drug Administration (FDA) has now launched an initiative to standardize the application of CFD to the assessment of haemolysis in blood pumps.…”
Section: Methodsmentioning
confidence: 99%